Feminism in India (Global Journal of Human-Social Science, 2016)
Feminism in Indian literature as can be most commonly conceived is a much sublime and over-the-top concept which is most subtly handled under restricted circumstances With advancement of time however feminism has been accepted in India setting aside the patriarchal predomination to certain extent Leaving aside the activists and crusaders of the political and social scenario perhaps massive work of feminism is also accomplished through Indian literature Yet prior to comprehending a more intense look into feminist literature in India it is necessary to grasp the essential concept of the term feminism in the country s context beginning from its inception The history of feminism in India can be looked at as principally a practical effort Beginning FROM the first inception of the Universe there is a fascinating myth associated with the creation of woman by the Supreme Creator Lord Brahma And indeed beginning from Brahma Himself the idea of feminism in Indian literature both oral and written had begun to be established though perhaps not as blatant as is today It is said that Brahma had first created man and in his generosity had desired to give man a companion But by then he had depleted all the material in the creation of man and hence he had borrowed umpteen components from the handsome creation of nature and had thus made woman out of them Lord Brahma had introduced woman to his earlier creation man stating She will serve you lifelong and if you cannot live with her neither can you live without her The primeval myth carries an unambiguous implication of woman s image in life and literature for centuries